Enhanced the visible light photocatalytic decomposition of antibiotic pollutant in wastewater by using Cu doped WO3. Issue 1 (February 2021) - Quyen, Vu Thi; Kim, JiTae; Park, Poong-Mo; Huong, Pham Thi; Viet, Nguyen Minh; Thang, Phan Quang
Graphical abstract: Highlights: Highly efficient visible light driven photocatalyst Cu doped WO3 was synthesized. Cu-WO3 can reduce the recombination rate of electron-hole and narrowed band gap energy. The Cu-WO3 had high recyclability and can reuse for 5 cycles. 92.7 % TC was decomposed from wastewater by Cu-WO3 / visible light. Abstract: Due to the rapid increase in the use of tetracycline (TC), a broad-spectrum antibiotic, the environmental residues of TC in water have aroused critical health issues. This work investigates the effectiveness and capability of Cu ions loaded WO3 (Cu-WO3 ) for the enhancement of photocatalytic decomposition of TC in wastewater. Different techniques were employed to characterize the catalyst such as XRD, XPS, FESEM, TEM and UV–vis. The optical properties analysis showed that Cu doped WO3 was successfully narrowed the bandgap energy, resulting in improved the removal efficiency of TC. Experimental results illustrate that Cu doping effectively improved the photocatalytic activity of WO3 and 2.5 %. wt. Cu doped exhibited the highest TC degradation efficiency (96.8 %). The photocatalytic decomposition of TC by Cu-WO3 was significantly increased under strongly alkaline conditions (pH 8–10). The reusability of catalysts and the leaching of transition metal ions was also investigated. After the fifth cycle, the photocatalytic degradation of TC by Cu-WO3 only reduced by 18.2 %, indicated that the Cu-WO3 can use as an excellent photocatalyst response for the TC degradation. The radical screening, the intermediates products and the proposed mechanism were discussed in detail. Finally, the Cu-WO3 was applied to remove TC from wastewater and it could efficiently remove 93.7 % TC within 60 min. Based on these findings, Cu-WO3 can use as a good candidate with long-time stability for photodegradation of TC in wastewater.